Russia’s Energy Efficiency Policies in the Industry Sector: Critical Perspectives - Bogoviz, Aleksei Valentinovich; Lobova, Svetlana Vladislavlevna; Ragulina, Yulia Vyacheslavovna; Alekseev, Alexander Nikolaevich (International Journal of Energy Economics and Policy, 2018)
The paper critically reviews the existing energy efficiency policies in the Russian industry sector with the purpose of analyzing their current state, processes of implementation, and main limitations and drawbacks. In particular, we focus on the most energy intensive industries: (a) ferrous metallurgy, (b) building materials production, (c) pulp and paper industry, and (d) fertilizer production. The paper carefully reviews the existing energy efficiency policies in Russia’s industry since 2008, focusing on the following dimensions: (a) government management system, (b) technological regulation, (c) financial incentives and funding, (d) supporting mechanisms. Then, on the basis of the data collected according to the methodology used by the Ministry of Energy of Russia, an analysis of energy efficiency performance in industry is conducted. Last, we critically discuss the results obtained, emphasize overall directions of the energy efficiency policies, and outline main limitations the methodology used by the Ministry of Energy of Russia to evaluate energy efficiency performance in the industry sector has. Keywords: Energy Efficiency, Industry, Russia. JEL Classifications: Q43, Q48, L60. DOI: https://doi.org/10.32479/ijeep.7005